GEOLOGICAL CONSEQUENCES OF AMORPHIZATION OF THE LITHOSPHERE AND UPPER MANTLE STRUCTURES CAUSED BY HYDROGEN DEGASSING - Iosif L. Gufeld (Геодинамика и тектонофизика)
Formation of the geological medium boundaries and patterns is specific, but such specific features have not been fully considered yet. No consideration is given to the nature of periodic variations of various parameters of the geological medium from the surface to the depth of the upper mantle. Remarkable are properties of interblock/interplate marginal structures that ensure steady and quite  contrasting movements of blocks, and it is of interest which processes provide for such properties. Another related question is why insignificant attention is still given to some variations of geophysical fields that might be interpreted as precursors of large-scale fracturing? Degassing (first of all, hydrogen degassing), P–T parameters at any depth level, and pressure of the upper layers determine the crystalline structure of the medium, including layers between blocks. Due to combinations of these impacts, principally new conditions are established, in which  amorphized/irregular and regular structures are formed. Such a twophase system, including a variable number of regular/crystalline and irregular/amorphized phases, may be responsible for specific and unique spatial geological structures, such as the Moho, blocks and ‘subduction’ zones, and variations of their parameters. The stable amorphized structure of the boundary  interlayers facilitates sliding of blocks against each other, which does not permit any control of transfer of movements to rapid displacements followed by strong earthquakes. This article considers the nature of processes that generate amorphized structures in the geological medium and geological consequences of such processes.